2022
DOI: 10.1038/s41598-022-24865-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and characterisation of Salicornia europaea, Tripolium pannonicum and Crithmum maritimum biomass for green biorefinery applications

Abstract: Salt-tolerant halophytes have shown potential for biorefinery and agricultural use in salt-affected soils, increasing the value of marginal lands. They could provide a bio-based source for compounds obtained from the petrochemical industry or an alternative for biomass currently imported overseas. Salicornia europaea, Tripolium pannonicum and Crithmum maritimum were cultivated in hydroponic systems under various salinity conditions, harvested green but not food-grade, and fractionated to green juice and fibre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 57 publications
3
38
0
Order By: Relevance
“…The results are aligned to those previously reported for other Salicornia spp., as Alassali et al [ 11 ] found 61.1% ash content of S. sinus-persica juice, and Christiansen et al [ 12 ] reported more than 80% of the total ash from the fresh S. bigelovii was recovered in the juice fraction after screw press. Changes in cultivation salinity do not only affect the ash content of plants but may also change the metabolism of sugars and lipids, which has been previously shown by Hulkko et al [ 13 ] and Duan et al [ 52 ] for S. europaea and Magni et al [ 53 ] for Salicornia perennis . The DM from lignified plants had a lower ash content than fibre residue from partly lignified plants, but rinsing with water could have removed some of the salts from the biomass surface.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The results are aligned to those previously reported for other Salicornia spp., as Alassali et al [ 11 ] found 61.1% ash content of S. sinus-persica juice, and Christiansen et al [ 12 ] reported more than 80% of the total ash from the fresh S. bigelovii was recovered in the juice fraction after screw press. Changes in cultivation salinity do not only affect the ash content of plants but may also change the metabolism of sugars and lipids, which has been previously shown by Hulkko et al [ 13 ] and Duan et al [ 52 ] for S. europaea and Magni et al [ 53 ] for Salicornia perennis . The DM from lignified plants had a lower ash content than fibre residue from partly lignified plants, but rinsing with water could have removed some of the salts from the biomass surface.…”
Section: Resultsmentioning
confidence: 72%
“…In this regard, two concepts can be applied, depending on the plant’s growth stage: green biorefinery from partly lignified plants or more traditional lignocellulose biorefinery from completely lignified plants after seed production. The green biorefinery approach, where the biomass is first fractionated to green juice and fibre residue, often targeting the production of biochemicals, feed products, and biofuels, has been previously tested for Salicornia sinus-persica , Salicornia bigelovii, Salicornia dolichostachya, and Salicornia europaea [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Research on the characterization of the plant has been carried out and the potential application of bioactive extracts in nutraceuticals, biopharmaceuticals, and cosmetics 27 given the presence of phenolic acids, avonols, organic acids, proteins, carbohydrates, and lipids. 28,29 Lately, the research of S. ramosissima applications has been carried out on food applications. [30][31][32] Other applications of S. ramosissima have been recently studied including as a source of cosmetics, 33 kitchen salt, 34 antioxidants 35 and biogas.…”
Section: Introductionmentioning
confidence: 99%
“…Halophytic biomass is receiving particular attention for the valorization of coastal areas and salt-affected lands, as these salt-tolerant plants can germinate under saline conditions without hindering their seeds or biomass production. These plants contain valuable ingredients that can be used for food, feed production, medical applications, and high-value-added compounds [1][2][3]. Furthermore, the residual organic matter of the halophyte biomass can be used for renewable energy production in the form of biogas via anaerobic digestion (AD).…”
Section: Introductionmentioning
confidence: 99%
“…This makes green halophytic biomass more amenable to AD, with a higher degradability and higher methane yields. Nevertheless, the composition of halophytic biomass with respect to the lignocellulosic fiber material may vary depending on the species, location, and growing conditions [2,5].…”
Section: Introductionmentioning
confidence: 99%